Blockchain and tokenized securities: The potential for green finance - Marco Schletz; Darius Nassiry; Myung-Kyoon Lee (Asian Development Bank Institute (ADBI), 2020)
Green investment vehicles are limited by multiple market failures, such as high transaction costs for certification and monitoring, and high minimum investment sizes. In this exploratory study, we apply an inductive approach based on qualitative evidence from expert feedback to assess the potential of blockchain-based security tokens to address these market failures. The tokenization of real assets or debt/equity instruments reduces transaction costs through disintermediation and automation, enhances transparency, and reduces size and liquidity requirements due to lower transaction costs. The main constraints to the adoption of tokenized securities are software risk, regulatory uncertainty, and immature investment infrastructure. These constraints can be addressed by decision- and policy makers in Asia. Through developing pilot use cases and establishing regulatory sandboxes for tokenized securities, valuable experiences and stakeholder feedback can be merged into coherent regulatory and investment frameworks. Even though tokenized securities are a nascent technology and currently limited by immaturities, it is important to consider and develop this financing mechanism in a proactive manner, given its high potential to democratize green finance.
Keywords: E40; E42; F34; F35; G00; G12; O3; 330; green finance; blockchain; tokenized securities; security token offering; Asia; green bonds; policy implications; climate change; sustainable development; climate finance; Paris Agreement; sustainability finance